Prekrškovno pravo: Praktikum - Dvojmoč, Miha (University of Maribor Press, 2023)
Minor Offences Act: Practicum. The essence of the Minor Offences Act practicum itself is to acquaint students with the law on minor offences, to understand general and fundamental concepts, to regulate minor offences and their sanctions, and to present a quick and regular misdemeanor procedure. The purpose of the practicum is to enable students to expand their horizons and acquire additional knowledge, while the exercises and instructions themselves encourage them to look for some information on their own. Practical examples presented throughout the practicum provide an additional explanation that helps students understand and relate theory to practice.